Available Virtual Reality-Based Tools for Executive Functions: A Systematic Review - Borgnis, Francesca; Baglio, Francesca; Pedroli, Elisa; Rossetto, Federica; Uccellatore, Lidia; Oliveira, Jorge Alexandre Gaspar; Riva, Giuseppe; Cipresso, Pietro (Frontiers in Psychology, 2022)
Introduction: Executive dysfunctions constitute a significant public health problem: their high impact on everyday life makes it a priority to identify early strategies for evaluating and rehabilitating these disorders in a real-life context. The ecological limitation of traditional neuropsychological tests and several difficulties in administering tests or training in real-life scenarios have paved the way to use Virtual Reality-based tools to evaluate and rehabilitate Executive Functions (EFs) in real-life. Objective: This work aims to conduct a systematic review to provide a detailed description of the VR-based tools currently developed for the evaluation and rehabilitation of EFs. Methods: We systematically searched for original manuscripts regarding VR tools and EFs by looking for titles and abstracts in the PubMed, Scopus, PsycInfo, and Web of Science databases up to November 2021 that contained the following keywords “Virtual Reality” AND “Executive function*.” Results and conclusion: We analysed 301 articles, of which 100 were included. Our work shows that available VR-based tools appear promising solutions for an ecological assessment and treatment of EFs in healthy subjects and several clinical populations.